Genetic diversity of Plasmodium vivax isolates from pregnant women in the Western Brazilian Amazon: A prospective cohort studyResearch in context - Jamille Gregório Dombrowski; Holly Acford-Palmer; Monica Campos; Erika Paula Machado Separovic; Sabrina Epiphanio; Taane Gregory Clark; Susana Campino; Claudio Romero Farias Marinho (Elsevier, 2023)
Summary: Background: Each year, 92 million pregnant women are at risk of contracting malaria during pregnancy, with the underestimation of the mortality and morbidity burden associated with Plasmodium vivax. During pregnancy, P. vivax infection is associated with low birth weight, maternal anaemia, premature delivery, and stillbirth. In the State of Acre (Brazil), high transmission leaves pregnant women at greater risk of contracting malaria and having a greater number of recurrences. The study of genetic diversity and the association of haplotypes with adverse pregnancy effects is of great importance for the control of the disease. Here we investigate the genetic diversity of P. vivax parasites infecting pregnant women across their pregnancies. Methods: P. vivax DNA was extracted from 330 samples from 177 women followed during pregnancy, collected in the State of Acre, Brazil. All samples were negative for Plasmodium falciparum DNA. Sequence data for the Pvmsp1 gene was analysed alongside data from six microsatellite (MS) markers. Allelic frequencies, haplotype frequencies, expected heterozygosity (HE) were calculated. Whole genome sequencing (WGS) was conducted on four samples from pregnant women and phylogenetic analysis performed with other samples from South American regions. Findings: Initially, the pregnant women were stratified into two groups-1 recurrence and 2 or more recurrences-in which no differences were observed in clinical gestational outcomes or in placental histological changes between the two groups. Then we evaluated the parasites genetically. An average of 18.5 distinct alleles were found at each of the MS loci, and the HE calculated for each marker indicates a high genetic diversity occurring within the population. There was a high percentage of polyclonal infections (61.7%, 108/175), and one haplotype (H1) occurred frequently (20%), with only 9 of the haplotypes appearing in more than one patient. Interpretation: Most pregnant women had polyclonal infections that could be the result of relapses and/or re-infections. The high percentage of H1 parasites, along with the low frequency of many other haplotypes are suggestive of a clonal expansion. Phylogenetic analysis shows that P. vivax population within pregnant women clustered with other Brazilian samples in the region. Funding: FAPESP and CNPq - Brazil.